Coupling of NMR to ACOMP for Terpolymerization Monitoring and Control. Issue 6 (7th November 2019) - McAfee, Terry; Jarand, Curtis W.; Zekoski, Thomas; Montgomery, Rick; Reed, Wayne F.
Abstract: Monitoring and control of free radical copolymerization using automatic continuous online monitoring of polymerization reactions (ACOMP) with UV detection has been recently achieved. It is difficult, however, to achieve spectral separation of similar monomers with UV alone. Here, nuclear magnetic resonance (NMR) is coupled to ACOMP for the first time and terpolymerization reactions involving acrylamide (Am), sodium acrylate (Ac), and styrene sulfonate (SS) are monitored, and a first attempt at active composition control is made. The NMR resolves the concentrations of Am and Ac, while the UV resolves SS and the sum of Am and Ac. NMR analysis is performed in water, using signal suppression, to eliminate the need for deuterated solvents. From this, instantaneous fractions of each comonomer in the terpolymer are continuously known, along with weight average molecular weight and intrinsic viscosity, IV. Am and Ac have similar reactivities, whereas the reactivity ratio of SS is much larger. Hence, there is high composition drift in batch polymerization and SS is rapidly consumed, leaving a final copolymer of Am and SS to form. Maintaining constant terpolymer composition is taken as a first step toward active control. Abstract : Adding a 60 MHz process nuclear magnetic resonance to the ACOMP detector train allowed, in conjunction with UV detection, continuous separation, and determination of three different monomer species during a terpolymerization reaction. Based on this, the first attempt at automatic composition control is made. Weight average molecular weight and reduced viscosity are simultaneously monitored.